Reproductive outcomes after fertility-sparing surgery for cervical cancer - results of the multicenter FERTISS study - Fricová, Lenka; Kommoss, Stefan; Scambia, Giovanni; Ferron, Gwenael; Kocián, Roman; Harter, Philipp; Anchora, Luigi Pedone; Bats, Anne-Sophie; Novàk, Zoltán; Walter, Christina Barbara; Raspagliesi, Francesco; Lambaudie, Eric; et al. (Gynecologic oncology, 2024)
INTRODUCTION: Fertility-sparing treatment (FST) for patients with cervical cancer intends to achieve oncologic outcomes comparable to those after radical treatment while maximizing reproductive outcomes, including the ability to conceive and minimizing the risk of prematurity. METHODOLOGY: International multicentre retrospective FERTISS study focused on patients treated with FST analysed timing of FST relative to pregnancy, conception attempts and methods, abortion rates, prophylactic procedures reducing the risk of severe prematurity, pregnancy duration, and delivery mode. RESULTS: Of the 733 patients treated at 44 centres in 13 countries, 49.7% attempted to conceive during median follow-up of 72 months and 22.6% (166/733) patients achieved a successful pregnancy. Success rate was significantly higher after non-radical surgery (63.2%; 122/193) compared to radical trachelectomy (25.7%; 44/171, p < 0.001). Available perinatological data shows that 89.5% (111/124) of the patients became pregnant naturally. There was no significant difference in the abortion rate in the first pregnancy nor delivery success rates between non-radical and radical procedures patients. Preterm delivery (<38 weeks gestation) occurred more frequently after radical than non-radical procedures (76.5% vs. 57.7%, p = 0.15). Almost all patients (97.3%; 73/75) who underwent regular ultrasound cervicometry in pregnancy with subsequent prophylactic procedures delivered a live fetus, compared to 30.6% (15/49) women without such management, p < 0.001. CONCLUSION: Patients who underwent non-radical surgery had significantly higher pregnancy rates. Most pregnancies resulted in a viable fetus, but radical trachelectomy led to a higher rate of preterm births in the severe prematurity range. Half of the patients did not attempt pregnancy after FST.
Keywords: Trachelectomy; Retrospective Studies; těhotenství; Cervical cancer; Fertility-sparing treatment; lidé; Premature Birth; výsledek těhotenství; Middle Aged; Adult; mladý dospělý; nádory děložního čípku; zachování plodnosti; Conization; Young Adult; ženské pohlaví; předčasný porod; retrospektivní studie; Humans; Pregnancy; Pregnancy Outcome; lidé středního věku; Uterine Cervical Neoplasms; dospělí; Female; trachelektomie; Fertility Preservation